1990
DOI: 10.1203/00006450-199002000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and Overnutrition in the Neonatal Rat: Long-Term Effects on Noradrenergic Pathways in Brain Regions

Abstract: ABSTRACT. To determine whether neonatal nutrition influences development of CNS noradrenergic systems, litter sizes were manipulated at birth to produce undernutrition (16-17 pupsllitter) or overnutrition (five to six pups) and compared to rats reared in normal litter sizes (10-11 pups). Studies were conducted throughout the preweaning period in which nutrition was manipulated, as well as during postweaning nutritional rehabilitation. Sparing of brain growth occurred, evidenced by much smaller changes in brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 18 publications
3
29
1
Order By: Relevance
“…Because SNS activity is under the direct control of centers in the hypothalamus and brain stem, it is likely that litter size affects the functional development of these regions as well. In support of this conjecture, Seidler and colleagues (24) showed that NE turnover within the cerebral cortex and cerebellum of the rat was affected by litter size in developing animals. More recently, Plagemann and colleagues (5,6,21,22) have demonstrated effects of litter size on the structure, neurochemistry, and responsiveness to leptin of neurons in the paraventricular, ventromedial, and arcuate nuclei of the hypothalamus.…”
Section: Ajp-regulatory Integrative Comp Physiolmentioning
confidence: 67%
See 2 more Smart Citations
“…Because SNS activity is under the direct control of centers in the hypothalamus and brain stem, it is likely that litter size affects the functional development of these regions as well. In support of this conjecture, Seidler and colleagues (24) showed that NE turnover within the cerebral cortex and cerebellum of the rat was affected by litter size in developing animals. More recently, Plagemann and colleagues (5,6,21,22) have demonstrated effects of litter size on the structure, neurochemistry, and responsiveness to leptin of neurons in the paraventricular, ventromedial, and arcuate nuclei of the hypothalamus.…”
Section: Ajp-regulatory Integrative Comp Physiolmentioning
confidence: 67%
“…Similarly, cardiac NE concentrations are inversely related to litter size at 15 days of age, although not at weaning (10). Finally, cardiac and renal NE levels are lower at 40 days of age in rats reared in large litters than in those reared in smaller litters (24). However, the consequences of litter size for sympathoadrenal function (in contrast to tissue NE levels) in adult animals has not been examined.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Noradrenaline (NA) is an upregulator of hypophysiotropic proTRH expression (Uribe et al 1993, Perello et al 2007. Importantly, brain NA concentrations in early-overfed animals are low (Seidler et al 1990), and the binding of adrenergic receptors in PVN is reduced in diet-induced obese rats (Levin 1996). This is also indicated by the reduced catecholamine release in caffeine-stimulated adrenal cells of early-overfed adult rats produced by litter reduction, as well as by low expression of the b2-adrenergic receptor evaluated in liver homogenates, which may lead to decreased peripheral sensitivity to catecholamines and lipolysis rate (Conceicao et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…33 Finally, changes in fetal or neonatal nutrition owing to the presence of maternal diabetes or variations in litter size, respectively, also exert effects on SNS development. 34,35 The effects associated with exposure to these environmental factors are not uniform. As the SNS is composed of numerous function-specific subdivisions, 36 however, development of each subunit is likely influenced by its own set of environmental factors.…”
Section: -16mentioning
confidence: 99%